An exploratory study of how casino dealer communication styles lead to player satisfaction - Hwang, Jinsoo; Park, Seulgi (Journal of travel & tourism marketing, 2018)
The purpose of this study is to verify the importance of communication styles in the casino industry. More specifically, it was proposed that nine types of casino dealer communication styles affect player satisfaction. In addition, it was hypothesized that player satisfaction plays an important role in the formation of trust, commitment, and loyalty. A conceptual model was developed and tested using the empirical data collected from 414 table game players in Korea. The results indicated that six dimensions of communication styles (i.e. attentive, open, friendly, relaxed, animated, and contentious) positively affect player satisfaction, which in turn has a positive influence on trust, commitment, and loyalty.